PENGARUH LINGKUNGAN KERJA FISIK DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT BPR NBP 12 TANGERANG SELATAN - Sulistia Wati Aliah; Laura Komala (Journal of Research and Publication Innovation, 2025)
This study aims to examine the influence of physical work environment on employee performance, the influence of work discipline on employee performance, as well as the simultaneous influence of physical work environment and work discipline on employee performance at PT BPR NBP 12. The research method used is a quantitative approach, with data collected through a questionnaire distributed to the entire population, which consists of 52 employees who also served as the research sample.Data analysis techniques include validity test, reliability test, classical assumption tests, multiple linear regression analysis, correlation coefficient test, coefficient of determination, and hypothesis testing using both t-test (partial) and F-test (simultaneous).The results show that the variable physical work environment (X1) has a significant partial influence on employee performance, as indicated by the value t-count (3.115) > t-table (2.009) and a significance level of 0.003 < 0.05. The work discipline variable (X2) also shows a significant partial influence on employee performance, with a t-count (5.358) > t-table (2.009) and a significance level of 0.001 < 0.05. Simultaneously, the physical work environment and work discipline have a significant influence on employee performance, as demonstrated by the F-count (38.943) > F-table (3.19) and significance level of 0.000 < 0.05.